Glucokinase mutations associated with non-insulin-dependent (type 2) diabetes mellitus have decreased enzymatic activity: implications for structure/function relationships. - Gidh-Jain, M (1993)
The glycolytic enzyme glucokinase plays an important role in the regulation of insulin secretion and recent studies have shown that mutations in the human glucokinase gene are a common cause of an autosomal dominant form of non-insulin-dependent (type 2) diabetes mellitus (NIDDM) that has an onset often during childhood. The majority of the mutations that have been identified are missense mutations that result in the synthesis of a glucokinase molecule with an altered amino acid sequence. To characterize the effect of these mutations on the catalytic properties of human beta-cell glucokinase, we have expressed native and mutant forms of this protein in Escherichia coli. All of the missense mutations show changes in enzyme activity including a decrease in Vmax and/or increase in Km for glucose. Using a model for the three-dimensional structure of human glucokinase based on the crystal structure of the related enzyme yeast hexokinase B, the mutations map primarily to two regions of the protein. One group of mutations is located in the active site cleft separating the two domains of the enzyme as well as in surface loops leading into this cleft. These mutations usually result in large reductions in enzyme activity. The second group of mutations is located far from the active site in a region that is predicted to undergo a substrate-induced conformational change that results in closure of the active site cleft. These mutations show a small approximately 2-fold reduction in Vmax and a 5- to 10-fold increase in Km for glucose. The characterization of mutations in glucokinase that are associated with a distinct and readily recognizable form of NIDDM has led to the identification of key amino acids involved in glucokinase catalysis and localized functionally important regions of the glucokinase molecule.